Interplay Between mTOR and Hippo Signaling in the Ovary: Clinical Choice Guidance Between Different Gonadotropin Preparations for Better IVF - Papageorgiou, Kyriaki; Mastora, Eirini; Zikopoulos, Athanasios; Grigoriou, Maria E.; Georgiou, Ioannis; Michaelidis, Theologos M. (Frontiers in Endocrinology, 2021)
One of the most widely used types of assisted reproduction technology is the in vitro fertilization (IVF), in which women undergo controlled ovarian stimulation through the administration of the appropriate hormones to produce as many mature follicles, as possible. The most common hormone combination is the co-administration of gonadotropin-releasing hormone (GnRH) analogues with recombinant or urinary-derived follicle-stimulating hormone (FSH). In the last few years, scientists have begun to explore the effect that different gonadotropin preparations have on granulosa cells’ maturation and apoptosis, aiming to identify new predictive markers of oocyte quality and successful fertilization. Two major pathways that control the ovarian development, as well as the oocyte–granulosa cell communication and the follicular growth, are the PI3K/Akt/mTOR and the Hippo signaling. The purpose of this article is to briefly review the current knowledge about the effects that the different gonadotropins, used for ovulation induction, may exert in the biology of granulosa cells, focusing on the importance of these two pathways, which are crucial for follicular maturation. We believe that a better understanding of the influence that the various ovarian stimulation protocols have on these critical molecular cascades will be invaluable in choosing the best approach for a given patient, thereby avoiding cancelled cycles, reducing frustration and potential treatment-related complications, and increasing the pregnancy rate. Moreover, individualizing the treatment plan will help clinicians to better coordinate assisted reproductive technology (ART) programs, discuss the specific options with the couples undergoing IVF, and alleviate stress, thus making the IVF experience easier.